Measuring the Impact of Inclusive Economic Growth; Empirical Study of SDGs in Indonesia - Anwar, Andi Faisal; Asnun, Angelina Putri; Abdul Wahab, (Technium Social Sciences Journal, 2021)
The purpose of this study is to measure the impact of inclusive economic growth as an SDGs agenda in Indonesia. The methodology of this research is to use a quantitative approach based on path analysis. The results of this study found that the unemployment rate has a positive effect on the Gini ratio or in other words has a directly proportional relationship. On the other hand, the gender development index, average length of schooling, and electricity consumption per capita have a negative effect on the Gini ratio, in other words showing an inverse relationship. Next, the unemployment variable and the Gini ratio both show an inverse relationship to economic growth. Meanwhile, the gender development index, average length of schooling, and electricity consumption per capita each have a positive effect on economic growth. Thus, each of these variables has an inverse relationship to economic growth. The implication of this research is that the government must be more aggressive in encouraging more inclusive development based on the strategic indicators contained in the SDGs to realize better socio-economic development. Keywords. Growth, Gini Ratio and SDGs